Assessment of minimum inhibitory concentration to vancomycin, tigecycline, linezolid, daptomycin, ceftaroline and mupirocin against methicillin resistant Staphylococcus aureus clinical isolates by antibiotic gradient strips - N., Aparna; P. R., Devipriya; N., Shilpa; Premanandan, Fashna; K. B., Anusree; Sathar, Saliha; Kumar K. S., Harish (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Staphylococcus aureus infections are one of the most common and serious hospital-acquired infections seen in developing countries. Methicillin resistant Staphylococcus aureus (MRSA) is an important human pathogen and normally colonized in body parts including skin, nose, perineum and throat. MRSA is resistant not only to all β-lactam groups but also other antibiotics including aminoglycosides, tetracycline and macrolides. In the present study the efficacy of agents used in the management of MRSA infections was determined by antibiotic gradient testing. Methods: A total of 60 clinical isolates of MRSA strains were collected from various diagnostic labs in central Kerala. Clinical isolates were reconfirmed as MRSA by gram staining, yellow-coloured colonies on mannitol salt Agar (MSA). Antibiotic susceptibility testing was done by disc diffusion method as recommended by CLSI guidelines. S. aureus isolates resistant to cefoxitin (30 µg) was identified as MRSA. Antibiotic gradient testing was performed to determine the MIC of vancomycin, tigecycline, linezolid, daptomycin, ceftaroline and mupirocin against MRSA isolates. Results: All the 60 MRSA isolates tested were sensitive to vancomycin, tigecycline, linezolid, daptomycin, ceftaroline and mupirocin (100%) and none of the MRSA isolates show resistance. Conclusions: Results of present study indicates that these agents may be used alongside vancomycin in management of infection caused by MRSA.